"Role of counselling services in eradicating social exclusion of underachieving secondary school students in ibadan " (2015)
"Social exclusion is a form of depriving an individual/ group of people from participating or benefiting from some factors /activities of which they have the right to partake from. This study therefore, examined the role of counselling services in eradicating social exclusion of underachieving students. A descriptive survey research design of an expost facto type was adopted. A total of 500 participants were randomly selected from underachieving secondary school students in Ibadan. 228 (45.6%) were males while 272 (54.4%) were females. The instruments used for the study were School Counselling services scale (SCSS) and Social Inclusion Scale (515). Data were analysed using Pearson's Product Moment Correlation and t-test tested at the 0.05 level of significance. The result showed that counselling has been perceived to be an effective tool in eradicating social exclusion among underachieving students in schools. It was therefore recommended that Counsellors should ensure to help students who may feel excluded or who show signs of isolation and truancy to ensure they are assisted to develop courage and determination to Improve. "